Reassessing the impact of natural landscape factors on spatial strategies in the Petra hinterland in Nabataean-Roman times - Kennedy, Will M. (Proceedings of the Seminar for Arabian Studies, 2016)
For any researcher acquainted with the landscape of Petra, the relation between archaeological sites and the natural landscape is immediately obvious. In most standard archaeological studies on Nabataean-Roman Petra (first century BC to second century AD) and its immediate environment, however, the natural landscape is often only briefly summarized in introductory chapters. As a result, its archaeological sites are not comprehensively contextualized within their natural environment. Archaeological investigations of the spatial distribution of sites and the cultural functioning of the landscape of Petra are still largely divorced from natural landscape factors. These factors can determine specific settlement locations and types, particularly when considering semi-nomadic cultures such as the Nabataeans. A more detailed and comprehensive study on the relationship between the natural landscape and Nabataean-Roman sites in the Petra area is therefore required. The aim of this paper is to present quantifiable data on this relationship based on field observations as well as modern landscape archaeological methodologies. This is only a small, but highly significant part of a more comprehensive and ongoing research project regarding the landscape organization and spatial strategies in the hinterland of Petra in Nabataean-Roman times.